Analysis of the improved mechanism of Rhodobacter sphaeroides VK-2-3 coenzyme Q10 by reverse metabolic engineering - Zhang, Long; Wang, Le-yi; Han, Yi-jun; Liu, Yan-xin; Li, Yong-li; Hu, Jian-hua; Tian, Zhi-jie; Liu, Zhan-ying (Frontiers in Microbiology, 2024)
Coenzyme Q10 (CoQ10) is an essential medicinal ingredient. In this study, we obtained a high-yielding mutant strain of CoQ10, VK-2-3, by subjecting R. sphaeroides V-0 (V-0) to a 12C6+ heavy ion beam and high-voltage prick electric field treatment. To investigate the mutation mechanism, the complete genomes of VK-2-3 and V-0 were sequenced. Collinearity analysis revealed that the nicotinamide adenine dinucleotide-dependent dehydrogenase (NAD) gene underwent rearrangement in the VK-2-3 genome. The NAD gene was overexpressed and silenced in V-0, and this construct was named RS.NAD and RS.ΔNAD. The results showed that the titers of CoQ10 in the RS.NAD and RS.ΔNAD increased and decreased by 16.00% and 33.92%, respectively, compared to those in V-0, and these differences were significant. Our results revealed the mechanism by which the VK-2-3 CoQ10 yield increases through reverse metabolic engineering, providing insights for genetic breeding and mechanistic analysis.